Opportunities of ICT as Integrated Approach in Classroom Practice - Gyawali, Rudra Hari; Sah, Ranadhir Kumar; Tamrakar, Kamal (JMC Research Journal, 2022)
This paper aims to motivate teachers and students to use information and technology (ICT) as an integrated approach to teaching mathematics. This article is prepared regarding the research question, "Why use ICTs in the classroom?" The research design of this study was qualitative. Two teachers and two students of the Bachelor of Business Management (BBM) third semester from two different colleges were the research sample, whereas the sampling was purposive. An in-depth interview and classroom observation of participants were the data collection methods, whereas the data collection tool was interview guidelines for both teachers and students. Teachers and students have to use ICTs in the classroom because it increases students' engagement and motivates them to learn. ICTs provide the opportunity for self-learning, teaching-learning and earning, student and teacher interaction, and create a student-friendly learning environment. So, teachers and students have to use ICTs in the classroom. This research is also recommended to policymakers, curriculum designers, educational institutions, teachers, and students to use the findings of this research to develop plans, curricula, infrastructure, environment, and learning behaviors that support ICT use. By doing so, education can be made more effective and engaging for all involved.